Impact of Single-Unit Transfusion on Patients Receiving Treatment for Acute Leukemia and Other Hematological Diseases - Alshehri, Nawaf Fayez; Alfaifi, Mohammed Salem Jubran; Aldawai, Aida Salah; Alzahrani, Rawan Ahmed Mohammed; alenazi- Name, Wedad awadh; ALZAHRANI, ABDULKHALIQ; ALSHAREEF, TURKI ABDULFATTAH; Tohary, Hassan Ali; Almenhali, Aidah Awadh; Alshenqiti, Reham; gaber, Mervat Ali Mostafa; Elfeky, Amany M (Journal of Ecohumanism, 2024)
Red blood cell (RBC) transfusions are a critical component of managing anemia in patients with acute leukemia and other hematological diseases. However, concerns regarding transfusion-related complications, resource utilization, and blood shortages have led to increased interest in restrictive transfusion strategies. This study evaluates the safety and efficacy of a single-unit RBC transfusion strategy compared to the conventional double-unit approach in hematological patients.This study including 200 patients undergoing treatment for acute leukemia or other hematological disorders. Patients were randomly assigned in a 1:1 ratio to receive either single-unit RBC transfusion (n = 100) or double-unit RBC transfusion (n = 100). The primary outcome was the composite incidence of severe complications, including ICU admission and 30-day mortality. Secondary outcomes included post-transfusion hemoglobin levels, transfusion-related adverse events, total RBC usage, hospital stay duration, and quality of life improvements. There were no significant differences between the single-unit and double-unit groups in ICU admission rates (12.3% vs. 11.8%, p = 0.72) or 30-day mortality (7.9% vs. 8.5%, p = 0.64). However, the single-unit group required significantly fewer transfusions (mean: 3.2 vs. 5.6 RBC units per patient, p < 0.001) and had longer transfusion intervals (10.3 vs. 8.1 days, p < 0.001). The hospital stay was shorter in the single-unit group (12.5 vs. 14.0 days, p = 0.03). While post-transfusion hemoglobin levels were higher in the double-unit group (9.3 vs. 8.5 g/dL, p < 0.001), this did not translate into improved clinical outcomes. Transfusion-related complications, particularly TACO, were more frequent in the double-unit group (4.0% vs. 1.7%, p = 0.05). The results demonstrate that a single-unit RBC transfusion strategy is non-inferior to the standard double-unit approach in terms of severe complications. Additionally, single-unit transfusion reduced overall RBC utilization, decreased transfusion-related complications, and shortened hospital stays. These findings support the adoption of restrictive transfusion protocols in hematological patients, especially in the context of blood shortages and resource optimization.